2016
DOI: 10.1016/j.neuron.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Synaptic Input Distribution in a Dendritic Computation of Motion Direction in the Retina

Abstract: Summary The starburst amacrine cell in the mouse retina presents an opportunity to examine the precise role of sensory input location on neuronal computations. Using visual receptive field mapping, glutamate uncaging, two-photon Ca2+ imaging, and genetic labeling of putative synapses, we identify a unique arrangement of excitatory inputs and neurotransmitter release sites on starburst amacrine cell dendrites: the excitatory input distribution is skewed away from the release sites. By comparing computational si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
169
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(185 citation statements)
references
References 45 publications
16
169
0
Order By: Relevance
“…Given the striking abundance of OSGCs in these two mammalian species, as well as reports of OSGCs in primates (Passaglia et al, 2002), it is likely that these cells directly contribute to orientation selectivity in higher visual centers. In line with this idea, several studies in rodents and primates have identified orientationselective neurons in noncortical areas, such as the dorsal lateral geniculate nucleus (dLGN; Cheong et al, 2013;Piscopo et al, 2013) and superior colliculus (Wang et al, 2010). Further supporting this possibility, recent studies have shown that mouse dLGN axonal projections provide orientation-selective inputs to primary visual cortex (Sun et al, 2016) and that inactivating primary visual cortex does not change the orientation tuning of dLGN neurons (Zhao et al, 2013).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Given the striking abundance of OSGCs in these two mammalian species, as well as reports of OSGCs in primates (Passaglia et al, 2002), it is likely that these cells directly contribute to orientation selectivity in higher visual centers. In line with this idea, several studies in rodents and primates have identified orientationselective neurons in noncortical areas, such as the dorsal lateral geniculate nucleus (dLGN; Cheong et al, 2013;Piscopo et al, 2013) and superior colliculus (Wang et al, 2010). Further supporting this possibility, recent studies have shown that mouse dLGN axonal projections provide orientation-selective inputs to primary visual cortex (Sun et al, 2016) and that inactivating primary visual cortex does not change the orientation tuning of dLGN neurons (Zhao et al, 2013).…”
mentioning
confidence: 90%
“…By comparison, our understanding of the mechanisms generating orientation selectivity in the retina is still rudimentary, largely due to the lack of specific molecular markers. Additionally, there is a drive to characterize the diversity of ganglion cell types, or feature channels, based on their functional, morphological, and genetic profiles (Baden et al, 2016). To date, how many OSGC types are present in the retina and how evolutionarily conserved they are across species remains unclear.…”
mentioning
confidence: 99%
See 3 more Smart Citations